Highly‐enhanced larval growth during the cold season mediated by the basking behavior of the butterfly Parnassius citrinarius (Lepidoptera: Papilionidae). Issue 3 (26th February 2013) - Akiyama, Koji; Nishida, Takayoshi
Abstract Some insect species are thought to grow quickly, even in low temperatures under natural conditions, presumably by conducting basking behaviors to use sunlight. However, whether basking behavior in fact enhances developmental speed and shortens the larval period in the field has not been determined. Moreover, few studies have examined whether basking is behavioral thermoregulation or simply the result of highly‐heterogeneous heat environments in the field. To examine these issues, we conducted field observations and laboratory experiments using larvae of Parnassius citrinarius Motschulsky, which mature within a short period after the thaw in early spring. First, body temperatures of larvae were measured under sunny and cloudy conditions. Second, larval preference for warmer locations was examined. Finally, we compared the developmental speed of larvae when they basked under field conditions and when did not bask in laboratory conditions under different air temperature regimes. Under sunny conditions, larval body temperature was substantially higher than either the temperature of the host plant or the air temperature, and was equivalent to the temperature of dead leaves, which the larvae used as basking sites. In contrast, no such tendency was observed under cloudy conditions. Larvae exhibited an exclusive preference for warmer locations. Moreover, in the field, despite the low ambient temperature, larvae grew much faster than those reared in the laboratory. These results imply that the basking behavior of P. citrinarius larvae is active thermoregulation to maintain high body temperatures in the cold season.